Hydrogeochemical Evolution of Groundwater Resource in an Arid Region of Southeast Iran (Ravar plain–Kerman province) - A. Qishlaqi; M. Abdolahi; A. Abbasnejad (Journal of Sciences, Islamic Republic of Iran)
This study was carried out in the Ravar plain, a typical arid zone in southeastern Iran, with the objectives of evaluating hydrochemical quality of the groundwater resources and identifying the processes that modify the groundwater composition. Groundwater samples were collected from representative wells spread over the study area. Major cations and anions along with physico-chemical parameters were measured as per the standard methods. The study approach includes conventional graphical plots and multivariate analysis of the hydrochemical data to define the hydrogeochemical evaluation of groundwater system based on the ionic constituents, water types and hydrochemical facies. The results indicated that the groundwater in the study area is alkaline (pH 7.1–7.8), hard (TH 350-4000 mg/l) and brackish (TDS 868–13000 mg/l). The Chadha’s diagram shows that the prevalent water type is Na–Cl–SO4, with alkali metals exceeding the alkaline earth metals. Gibbs and Durov diagrams as well as ionic ratio plots indicated that evaporation, water–rock interaction and ion exchange are the main processes that regulate the groundwater quality. It was also found that the majority of groundwater samples are undersaturated with respect to evaporitic minerals and oversaturated with respect to carbonate minerals. The application of principal component analysis resulted in two PCs. PC I with loading on Cl-, Na+, SO4-2, EC, and Ca+2 which is related to degree of groundwater mineralization while PC II with opposite loadings of HCO3- and pH. The findings of the study may be applicable to areas with similar characteristics elsewhere in arid regions.